1982
DOI: 10.1056/nejm198212093072403
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccine in Medical Staff of Hemodialysis Units

Abstract: We evaluated the efficacy of hepatitis B vaccine (Heptavax-B) containing only the ad subtype in a randomized, placebo-controlled, double-blind trial among 865 staff members of 43 hemodialysis units in the United States. Surface antibody developed in 92.6 per cent of the subjects after two doses of vaccine and in 96 per cent after the six-month booster. The incidence of infections with hepatitis B virus (with or without hepatitis) was 9.9 per cent in placebo recipients and 2.2 per cent in vaccine recipients (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(71 citation statements)
references
References 17 publications
1
69
0
1
Order By: Relevance
“…Multiple long-term immunogenicity and efficacy trials of the current licensed hepatitis vaccine have defined a protective anti-HBsAg level as Ͼ10 mIU͞ml (8)(9)(10)(11). In mice fed HBsAgtransgenic potatoes, anti-HBsAg antibodies were first detected 1 week after two doses; the response was increased to a peak value of 103 mIU͞ml 4 weeks after the third dose (Fig.…”
Section: Figmentioning
confidence: 99%
“…Multiple long-term immunogenicity and efficacy trials of the current licensed hepatitis vaccine have defined a protective anti-HBsAg level as Ͼ10 mIU͞ml (8)(9)(10)(11). In mice fed HBsAgtransgenic potatoes, anti-HBsAg antibodies were first detected 1 week after two doses; the response was increased to a peak value of 103 mIU͞ml 4 weeks after the third dose (Fig.…”
Section: Figmentioning
confidence: 99%
“…What we do not know, is whether this cross-reactive T cell response alone yields any protection against a HBV infection. But because HBsAg vaccinations are a very effective measure against a new infection [25,26] , it seems that a concurrent B cell response (i.e. protective anti-HBsAg titer) is primarily necessary to prevent HBV replication.…”
Section: Weihrauch Mr Et Al T-cell Response In Hepatitis Bs Non-respmentioning
confidence: 99%
“…Antibodies to the 'a' determinant confer protection against all subtypes of HBV. 8 Mutations in the HBV S gene have been reported in OLT recipients who developed HBV reinfection despite prophylaxis with monoclonal or polyclonal hepatitis B surface antibody (anti-HBs). McMahon et al found amino acid substitutions in the 'a' determinant in all three patients who were reinfected despite monoclonal anti-HBs prophylaxis, 9 while the incidence of mutations in the 'a' determinant in OLT recipients who were reinfected despite HBIG prophylaxis varied from 0% to 33%.…”
mentioning
confidence: 99%